IMPROVING STUDENTS` READING COMPREHENSION THROUGH COLLABORATIVE STRATEGIC READING (CSR) - Ni Ketut Kusumawati; Jim Ronni Tuna; Jennie Posumah (English Education Department, 2022)
The goal of this research was to examine whether or not Collaborative strategic reading (CSR) might increase students' reading comprehension. In this study, students struggled to understand narrative texts. Researchers used one class with pre-experimental design, and the sample consisted of 28 students of class X High School Swadharma Werdhi Agung. Multiple choice is a method of data collection. Before being given treatment, students were given a pre-test and after ended treatment, students were given post-test. Based on calculations, the results of the data analysis show that the average value in the pre-test is 46.25, while the average value in the post-test is 81.42. The findings show that there is an increase between the pre-test and post-test values. This shows that CSR was able to improve the understanding of reading students in the class X of the Swadharma Werdhi Agung High School. Conclusion: Collaborative Strategic Reading (CSR) succeeds, and it is recommended that English instructors use it to teach understanding of reading narrative text.